2019
DOI: 10.1108/ecam-06-2019-0288
|View full text |Cite
|
Sign up to set email alerts
|

Environmental sustainability of off-site manufacturing: a literature review

Abstract: Purpose Off-site manufacturing (OSM) is a modern method of construction that brings various environmental sustainability benefits for stakeholders. The increasing take-up of OSM in practice has attracted much research interest in its environmental sustainability. However, a holistic understanding of these previous research studies is still lacking. Therefore, the purpose of this paper is to critically review the existing body of knowledge regarding the environmental sustainability of OSM. Design/methodology/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 83 publications
0
26
0
Order By: Relevance
“…According to Jaillon et al [34], prefabrication application increased the average construction and demolition waste reduction level to 52%. On the one hand, the application of prefabricated construction combined with some emerging technologies, such as Building Information Modelling (BIM, a developing technology to form, organize, and manage throughout the construction project [35], radio frequency identification (RFID, a technology that used radio waves to identify objects [36], and Internet of Things (IoT, a new technology paradigm that was conceived to realize the interaction of machines and devices around the world [37]), reduced the production of construction waste at sources [5,38]. On the other hand, during the manufacturing stage, a large amount of wet work was transferred to the factory, prefabricated components were produced in a mechanized, standardized, and intelligent production line, resulting in a significant reduction in waste generation [39].…”
Section: Environmental Sustainabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…According to Jaillon et al [34], prefabrication application increased the average construction and demolition waste reduction level to 52%. On the one hand, the application of prefabricated construction combined with some emerging technologies, such as Building Information Modelling (BIM, a developing technology to form, organize, and manage throughout the construction project [35], radio frequency identification (RFID, a technology that used radio waves to identify objects [36], and Internet of Things (IoT, a new technology paradigm that was conceived to realize the interaction of machines and devices around the world [37]), reduced the production of construction waste at sources [5,38]. On the other hand, during the manufacturing stage, a large amount of wet work was transferred to the factory, prefabricated components were produced in a mechanized, standardized, and intelligent production line, resulting in a significant reduction in waste generation [39].…”
Section: Environmental Sustainabilitymentioning
confidence: 99%
“…The air pollution produced by conventional construction methods involves carbon emission and on-site dust. Numerous scholars have compared the lifecycle greenhouse gas (GHG) emission of the prefabricated building with that of conventional building and revealed that prefabricated construction methods reduced GHG emissions [5,40,41]. Some studies even integrated digital technologies to achieve real-time monitoring of carbon and GHG emissions.…”
Section: Environmental Sustainabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…This requires the integration of sustainability factors and knowledge in different building phases (such as manufacturing, assembly, and operation and maintenance) [3,4]. However, unlike conventional construction methods, offsite constructuion requires the evaluation of sustainability in the design stage [5,6]. The United Kingdom (UK), Singapore, and Hong Kong governments have identified Design for Manufacture and Assembly (DfMA) as the way to accelerate the efficiency and sustainability of the construction industry [4,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that prefabricated construction an alleviate the negative effects (e.g. massive waste from construction and demolition) on the environment from construction activities (Cao et al , 2015; Hu and Chong, 2019), increase production efficiency, shorten the construction duration (Richard, 2005), decrease the labor demand and reduce maintenance expenses (Hong et al , 2018). These advantages provide an explanation for the implementation of prefabricated construction, which has been embraced globally.…”
Section: Introductionmentioning
confidence: 99%